Adsorption of Cationic and Anionic Dyes onto Commercial Kaolin - D. Ziólkowska; A. Shyichuk; I. Karwasz; M. Witkowska (Adsorption Science & Technology)
Commercial kaolin from a Polish deposit has been examined as a low-cost adsorbent for effluent remediation using five cationic and five anionic industrial dyes. Methylene Blue dye was also used as a reference. The anionic dyes studied showed no affinity towards the kaolin surface, whereas the experimental isotherms for the adsorption of the cationic dyes could all be well described by the Langmuir equation. The values of the adsorption capacity of kaolin towards the cationic dyes ranged from 4 mg/g to 29 mg/g, being probably dependent on the geometry of the dye molecules. The resulting degrees of decolourization attained values of 85–90% for initial dye concentrations in the range 6–20 mg/dm 3 and for kaolin loadings of 0.5–3 g/dm 3 . Adsorption of the cationic dyes onto kaolin increased at higher solution pH values.